Pregnant mothers' awareness of rheumatic diseases in Balqa Governorate: A study of maternity center visits - M. Rifaei, Sufian.; Maqableh, Ghaith; Ghazal, Bandar; Akel, Alaa; Marji, Raya; Marwan Nagaway, Mohammadkhier (Journal of Neonatal Surgery, 2025)
This study aims to analyze the level of awareness and knowledge amongst pregnant women about rheumatic diseases and the relevant potential impact on pregnancy, and to examine the relationship between certain demographic variables (such as age, education, and health insurance) and this awareness. Data were collected via a questionnaire directed at 281 pregnant women in Balqa Governorate, Jordan. Data collection period spanned from February 20 to April 20, 2025. The chi-square test was used to analyze the relationships between the main variables. The results showed that most participants were aware of the term "rheumatic diseases," but awareness of their effects on pregnancy was limited, especially among those with limited education. The study also revealed a significant disparity in awareness between financially insured and uninsured women, reflecting the need to improve awareness, especially in communities with less access to health services. The study recommends strengthening educational efforts about rheumatic diseases, making medical information more available to uninsured women, and intensifying awareness campaigns in maternity centers.